Pharmacokinetics and Pharmacodynamics of Tildipirosin Against Pasteurella multocida in a Murine Lung Infection Model - Zeng, Dongping; Sun, Meizhen; Lin, Zhoumeng; Li, Miao; Gehring, Ronette; Zeng, Zhenling (Frontiers in Microbiology, 2018)
Tildipirosin, a 16-membered-ring macrolide antimicrobial, has recently been approved for the treatment of swine respiratory disease (SRD) and bovine respiratory disease (BRD). This macrolide is extensively distributed to the site of respiratory infection followed by slow elimination. Clinical efficacy has been demonstrated in cattle and swine clinical field trials. However, the pharmacokinetic/pharmacodynamic (PK/PD) index that best correlates with the efficacy of tildipirosin remains undefined. The objective of this study was to develop a PK/PD model following subcutaneous injection of tildipirosin against Pasteurella multocida in a murine lung infection model. The PK studies of unbound (f) tildipirosin in plasma were determined following subcutaneous injection of single doses of 1, 2, 4, 6, and 8 mg/kg of body weight in neutropenic lung-infected mice. The PD studies were conducted over 24 h based on twenty intermittent dosing regimens, of which total daily dose ranged from 1 to 32 mg/kg and dosage intervals included 6, 8, 12, and 24 h. The minimum inhibitory concentration (MIC) of tildipirosin against P. multocida was determined in serum. The inhibitory effect Imax model was employed for PK/PD modeling. The area under the unbound concentration-time profile over 24 h to MIC (fAUC0-24h/MIC) was the PK/PD index that best described the antibacterial activity in the murine infection model. The fAUC0-24h/MIC targets required to achieve the bacteriostatic action, a 1-log10 kill and 2-log10 kill of bacterial counts were 19.93 h, 31.89 h, and 53.27 h, respectively. These results can facilitate efforts to define more rational designs of dosage regimens of tildipirosin using classical PK/PD concepts for the treatment of respiratory diseases in pigs and cattle.